Numerical Comparison of Tubular Joint Strength in Offshore Codes - Sambu Potty, Narayanan (2010)
The increasing demand for oil and gas has propelled the continuous development of the design of offshore structures. These structures are used to support oil and gas exploration and production facilities above the elevation of waves. Welded tubular joints play a very important part in the safety of offshore structures. The design of these follows the Working Stress Design format in Malaysia. Worldwide, there is an extensive effort in developing and applying LRFD based standards. Recently, ISO code has been published, which proposes new design provision for design of tubular joints. This code contains factors that, mostly, reflect the environmental conditions of Gulf of Mexico and North Sea, where the conditions differ from the Malaysia. To adopt this code, calibration of the load and resistance factors is necessary, such that it meets the existing reliability indices. This adjustment of the load and resistance factors permits a specific design criteria and flexible safety margins with respect to the type of structure and environmental exposure resulting in an optimum system performance and economical cost-benefit design of new or reassessment of old offshore structures. As part of an ongoing research, this paper presents a numerical comparison of API RP2A WSD (21st edition including 2nd supplement), API RP2A LRFD and ISO 19902. All the codes follow the same basic formulations for predicting the strength of tubular joints, for both axial and moment capacities. The difference occurs in the basic strength factor (Qu) and the chord loads factor (Qf). To provide uniformity for the comparison, the resistance factors and safety factors are taken as unity. The API RP2A WSD 2nd Supplement, which was released after the ISO, incorporates more changes, as it is based on the latest research.